Development of the Use of Prezi Media on Short Story Writing Skills for Class Xi Indonesian Language Learning - Eliza Novita Wulandari (Institute of Multidisciplinary Research and Community Service, 2022)
Abstract: Learning media is a paraga tool that is useful as an intermediary in the process of conveying learning information so that it will have a big influence on learning success. One of the varied learning media is prezi, where the lesson material will be displayed in the form of online presentation media and includes illustrations and explanations of the material. The aim of this research is to determine the feasibility of Prezi-based learning media in short story writing skills in Indonesian language learning and determine students' responses to Prezi-based learning media in short story writing skills in Indonesian language learning. Keywords: prezi learning media, short stories, Indonesian language.